Sensitivity of boundary layer parameterization schemes in a marine boundary layer jet and associated precipitation during a coastal warm-sector heavy rainfall event - Shen, Yian; Du, Yu (Frontiers in Earth Science, 2023)
The sensitivity of planetary boundary layer (PBL) parameterization schemes in the Weather Research and Forecasting Model is investigated in simulating a marine boundary layer jet (BLJ) over South China Sea and associated coastal precipitation during a warm-sector heavy rainfall event (19-20 May 2015) near the coast of South China. Six PBL parameterization schemes are examined including YSU, MYJ, MYNN, ACM2, BouLac and UW schemes. The results show that YSU, MYJ, MYNN and BouLac schemes can generally reproduce the coastal warm-sector heavy rainfall with 6-h accumulated precipitation exceeding 50 mm, but not for the ACMs and UW schemes. No convection initiation occurs in the ACM2 run, while rainfall is located to further north with weaker intensity in the UW run. Meanwhile, weakest and strongest BLJs are simulated in the ACM2 and UW runs, respectively. In the ACM2 run, the weaker BLJ with the maximum wind speed less than 17 m·s-1 induces weaker convergence and lifting in the upwind side of the coastal terrain as well as less water vapor transport to the coastal area, which thus inhibit convection initiation. On the contrary, the too strong BLJ in the UW run with large area of wind speed greater than 18 m·s-1 causes the northward movement of convection along with cold pools, and rainfall moves further north accordingly. The differences in BLJs’ strength among PBL schemes are attributed to varying simulated low-level vortex on the northern side of the BLJ through veering ageostrophic winds. The intensity of the simulated low-level vortex is affected by variations in boundary layer mixing over land and associated vertical temperature stratification under different PBL schemes.